Implementation of The Adiwiyata Program by The Principal to Foster Students’ Morals towards The Environment - Ananda Mey Zaliyanti; Mohammad Zakki Azani (Yayasan Letiges Konsultan Sosial, 2024)
This study discusses the Adiwiyata Program implemented at Junior High School (SMPN) 2 Tanon. Adiwiyata is an environmental program in Indonesia that aims to increase school environmental awareness. This program encourages schools to integrate or include environment-related education in the curriculum. This research is qualitative with field research with data collection using case study techniques. Interviewing, observing, and documenting were the methods used for data collection. Data were analysed using interactive data analysis: data collection, reduction, presentation, and conclusion drawing. This research aims to find out how the principal implemented the Adiwiyata Program to foster students' morals towards the environment. The results of this study indicate that the principal has several programs that can support the implementation of the Adiwiyata program at the school; the programs implemented include: Including Adiwiyata in the learning curriculum, incorporating Adiwiyata values into the independent curriculum P5 project, implementing PHBS (Healthy Clean Living Behavior) and Go Green to students and teachers, carrying out daily pickets, carrying out Friday Kelingan Taman activities, making small parks, utilising organic and non-organic waste, and planning new programs. These activities refer to implementing the school's vision and mission to realise a healthy Adiwiyata school and form school members to have morals of caring for the environment.